Comparison of the consequences of state of charge and state of health on the thermal runaway behavior of lithium ion batteries. (June 2023) - Doose, Stefan; Hahn, Alexander; Fischer, Steffen; Müller, Jannes; Haselrieder, Wolfgang; Kwade, Arno
Abstract: In this work the influence of the SoC and the SoH on the thermal runaway was analyzed in depth (SoC 30–100 % /SoH 75–100 %). Generally, the results show a decrease in the strength of the TR reactions with decreasing SoC/SoH. The determined surface temperatures decrease by >100 °C when SoC and SOH are reduced to 50 % SoC or 75 % SoH because there are fewer stored and active lithium ions as well as less overall stored energy and more inactive components. Released particles and gas caused a mass loss reduction of 12.5 % (SoC) and 7 % (SoH), respectively, with measurable gas concentrations of decomposition products and linear hydrocarbons decreasing. At the same time the concentrations of gaseous electrolyte components increase. A comparative analysis at SoC 80 % or SoH 80 % shows that the amount of stored energy or Li-ions incorporated at the time of penetration into the anode is responsible for the main reaction characteristics, which include the course of the voltage drop, the temperature evolution and the composition of the reaction gases. However, despite aging effects occurring with SoH reduction, the surface temperatures and determined gas concentrations reach the same values. At microscopic scale, changes in the reactions, e.g. SEI-decomposition, are expected, but no effect on the macroscopic TR is measurable. In general, it has been shown that both lower SoC and SoH minimize the severity of an occurring TR. In summary, it could be determined that cell surface temperatures drop by the same average values, up to 100 °C, for the same reduction in SoC and SoH. Gas concentrations decrease, as do cell mass loss parameters. With lower energy, the amount of carbonate compounds in the gas phase increases, with decomposition products increasing with increased energy. In general, it has been shown that both lower SoC and SoH minimize the severity of an occurring TR. In a comparative analysis of decreased SoC and SoH, it was shown that the type of decrease in stored Li-ion amounts, setting SoC 80 % or SoH 80 %, does almost not affect the macroscopically detectable responses of TR. The surface temperatures reached on the cell, as well as the gas concentrations determined and parameters such as the penetration depth to the TR and the mass loss show identical values for SoC 80 % and SoH 80 %. In the final analysis, it is the quantity of stored Li-ions that determines the effects and strength of the TR, and effects such as cyclic aging or state of charge are negligible on a macroscopic level. The results help to better allocate the effects of aging and charging to the utilization phase and existing hazards, and form the basis for further predictions and simulations. Highlights: Influence of SoC and SoH on the safety behavior of lithium ion batteries is determined. Investigation of temperature development and certain key parameters of the TR Continuous time-resolved measurement of hazardous gaseous reaction products Identification of the free mobile Li amount in the anode as a detection parameter for the TR hazard of a LiB